Ultrasound-activated particles as CRISPR/Cas9 delivery system for androgenic alopecia therapy - Ryu, Jee Yeon; Won, Eun Jeong; Lee, Han A.Reum; Kim, Jin Hyun; Hui, Emmanuel; Kim, Hong Pyo; Yoon, Tae Jong (Biomaterials, 2020)
Compared to a plasmid, viral, and other delivery systems, direct Cas9/sgRNA protein delivery has several advantages such as low off-targeting effects and non-integration, but it still has limitations due to low transfer efficiency. As such, the CRISPR/Cas9 system is being developed in combination with nano-carrier technology to enhance delivery efficiency and biocompatibility. We designed a microbubble-nanoliposomal particle as a Cas9/sgRNA riboprotein complex carrier, which effectively facilitates local delivery to a specific site when agitated by ultrasound activation. In practice, we successfully transferred the protein constructs into dermal papilla cells in the hair follicle of androgenic alopecia animals by microbubble cavitation induced sonoporation of our particle. The delivered Cas9/sgRNA recognized and edited specifically the target gene with high efficiency in vitro and in vivo, thus recovering hair growth. We demonstrated the topical application of ultrasound-activated nanoparticles for androgenic alopecia therapy through the suppression of SRD5A2 protein production by CRISPR-based genomic editing.
Keywords: Androgenic alopecia; Micro-bubble; Nanoliposome; Protein delivery; Protein production; Topical application; Transfer efficiency; Ultrasound activations; Alopecia; Animals; Clustered Regularly Interspaced Short Palindromic Repeats; CRISPR-Associated Protein 9; CRISPR-Cas Systems; Gene Editing; Androgenic alopecia; Gene editing; Microbubble; Nanoliposome; Protein delivery